1998
DOI: 10.1002/(sici)1099-1026(1998090)13:5<289::aid-ffj750>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial properties of the linalol-rich essential oil ofHyssopus officinalis L. vardecumbens (Lamiaceae)

Abstract: The antimicrobial activity of essential oil of Hyssopus ocinalis L. var decumbens (Jordan & Fourr.) Briq. from France (Banon) and Hyssopus ocinalis L. from Italy (Piedmont) was studied taking account of their chemical composition determined by GC and GC±MS. Pinocamphone and isopinocamphone are present in H. ocinalis (4.4% and 43.3%, respectively), according to the ISO 9841 Standard (1991 E) but they are lacking in var. decumbens, where linalol (51.7%), 1,8-cineole (12.3%) and limonene (5.1%) instead are predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 2 publications
4
63
0
7
Order By: Relevance
“…Briq. is morphologically different from Hyssopus officinalis L. and is peculiar for its lack of pinocamphone (34).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Briq. is morphologically different from Hyssopus officinalis L. and is peculiar for its lack of pinocamphone (34).…”
Section: Resultsmentioning
confidence: 97%
“…The chemical composition of hyssop oil varies considerably, even between oils obtained from different samples of the same variety of hyssop (34). Volatile oil composition of hyssop varies also in dependence on growth stage or climatic conditions (35).…”
Section: Resultsmentioning
confidence: 99%
“…[17À19, 31,32] Most reports about the antifungal activity of hyssop oil are focused on its inhibitory effect against phytopathogenic and mycotoxin-producing fungi. [20,33À35] In contrast, there are only scarce studies about its anticandidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the anticandidal activity of hyssop oil has mostly been determined against reference strains of C. albicans, but less is known about its activity against clinical isolates, especially against NAC species. For example, Mazzanti et al [31] and Kizil et al [19] reported strong antimicrobial activity of essential oil from H. officinalis L. against C. albicans, C. tropicalis and C. krusei. On the contrary, according to other authors, hyssop oil demonstrates only moderate to weak antifungal activity.…”
Section: Introductionmentioning
confidence: 99%
“…decumbens was rather bactericidal. This higher antibacterial activity can be caused by linalool and higher content of 1,8-cineole while limonene is apparently responsible for the effect of volatile oil against molds in both variants of hyssop (MAZZANTI et al 1998).…”
Section: Effects Of Volatile Oil and Other Extractsmentioning
confidence: 99%